A student-led pilot lecture in nutrition as a catalyst for curriculum change: A case study from one medical school - Akash Patel; Ritika Modi; William McGonigle; Gauri Agarwal (PLoS ONE, 2026)
Background Poor diet is the leading cause of global disability and premature death, contributing to 11 million deaths annually. Despite this, nutrition remains underemphasized in medical education, with over 70% of United States (U.S.) medical schools failing to meet the National Research Council’s 1985 recommendation of 25 hours of nutrition training. In 2022, the U.S. House of Representatives passed a bipartisan resolution calling for meaningful nutrition education for health professionals. Amid this gap, unreliable media sources frequently shape patient nutrition knowledge rather than professional sources such as registered dietitians or licensed physicians. Strengthening interprofessional collaboration with nutrition professionals could enhance dietary counseling and patient care. Methods In response, one student implemented and evaluated the usefulness of a clinical nutrition lecture at the University of Miami Miller School of Medicine (UMMSM). Resulting student enthusiasm catalyzed the formation of a 50-member taskforce formed to expand and integrate nutrition longitudinally. A pre- and post-lecture survey around the session (Npre = 98, Npost = 77) assessed knowledge, perceptions of nutrition training, and comfort with dietary counseling. Results Knowledge of evidence-based nutrition improved significantly (p < .001). Post-lecture, students reported greater confidence applying nutrition in clinical practice and increased interest in lifestyle medicine training (p < .001). Conclusions After the session, there was increased self-reported confidence and understanding of nutrition’s role in health amongst students. Resulting student enthusiasm catalyzed the formation of a 50-member taskforce formed to expand nutrition education longitudinally with additional lectures to be integrated into the curriculum. This trajectory illustrates how even a small pilot can stimulate institutional dialogue and student-led momentum. We discuss key elements of an effective, multifaceted nutrition curriculum and propose a roadmap adaptable to other institutions.